Structure Integrity Analysis Using FluidStructure Interaction at Hydropower Bottom Outlet Discharge - Mohd Radzi M.R.; Zawawi M.H.; Abas M.A.; Ahmad Mazlan A.Z.; Mohd Arif Zainol M.R.R.; Hassan N.H.; Che Wan Zanial W.N.; Dullah H.; Kamaruddin M.A. (MDPI, 2024)
Dam reliability analysis is performed to determine the structural integrity of dams and, hence, to prevent dam failure. The Chenderoh Dam structure is divided into five parts: the left bank, right bank, spillway, intake section, and bottom outlet, with each element performing standalone functions to maintain the overall Dams continuous operation. This study presents a numerical reliability analysis of water dam reservoir banks using fluidstructure interaction (FSI) simulation of the bottom outlet structures operated at different discharge conditions. Three-dimensional computer-aided drawings were used to view the overall Chenderoh Dam. Next, a two-way fluidstructure interaction (FSI) model was developed to explore the influence of fluid flow and structural deformation on dam systems. The FSI modeling consists of Ansys Fluent and Ansys Structural modules to consider the boundary conditions separately. The reliability and performance of the reservoir bottom outlet structure was effectively simulated and recognised using FSI. The maximum stress on the bottom outlet section is 18.4 MPa, which is lower than the yield stress of mild steel of 370 MPa. Therefore, there will be no structural failure being observed on the bottom outlet section when the butterfly valve is fully closed. With a few exceptions, the FSI models projected that bottom outlet structures would be able to run under specified conditions without structural collapse or requiring interventions due to having lower stress than the materials yield strength. 2023 by the authors.